Dynamics of Educational Problems at SMA Negeri 1 Modoinding - Hamsah Hamsah; Paulus Robert Tuerah; Vidi E. Korompis; Sudirman Muhammadiyah; Frenki Batas; Miftahul Jannah; Romi Mesra (Journal on Education, 2023)
The aim of this research is to explain the dynamics of educational problems at SMA Negeri 1 Modoinding. The method used in this research is a qualitative research method. Data collection methods include observation, interviews, and documentation. The observation sheet was used as a research instrument. The research findings reveal that in conclusion, as we already know, there are still many students who experience difficulties such as student delinquency such as promiscuity, truancy during class hours, and Lack of Learning Facilities, one of which is at SMA Negeri 1 Modoinding. This can happen due to factors outside the school, such as incomplete families which have an impact on students' education, or because teachers do not educate children enough, making students feel free to do bad things at school. To overcome this problem, efforts need to be made to improve teacher quality, curriculum flexibility and the availability of educational facilities. Diverse teaching approaches, as well as a more holistic approach to student evaluation, must be addressed. Schools and the government must also focus more on career orientation and preparing students for the world of work or college